2004
DOI: 10.1002/gcc.20060
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic classification of relapsing favorable histology Wilms tumor using cDNA microarray expression profiling and support vector machines

Abstract: Treatment of Wilms tumor has a high success rate, with some 85% of patients achieving long-term survival. However, late effects of treatment and management of relapse remain significant clinical problems. If accurate prognostic methods were available, effective risk-adapted therapies could be tailored to individual patients at diagnosis. Few molecular prognostic markers for Wilms tumor are currently defined, though previous studies have linked allele loss on 1p or 16q, genomic gain of 1q, and overexpression fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 44 publications
(46 reference statements)
0
31
0
4
Order By: Relevance
“…To date, expression profiling studies have provided inconsistent results, perhaps due to the cellular heterogeneity found in WT, whereas genomic copy number analyses look more promising to discriminate relapsing tumors [20][21][22]. This is consistent with the predictive value of allele loss at chromosomes 1p and 16q found in the large NWTS-5 trial, although the critical genes or pathways remain to be defined [23].…”
Section: Filippo Spreaficomentioning
confidence: 63%
“…To date, expression profiling studies have provided inconsistent results, perhaps due to the cellular heterogeneity found in WT, whereas genomic copy number analyses look more promising to discriminate relapsing tumors [20][21][22]. This is consistent with the predictive value of allele loss at chromosomes 1p and 16q found in the large NWTS-5 trial, although the critical genes or pathways remain to be defined [23].…”
Section: Filippo Spreaficomentioning
confidence: 63%
“…Other promising prognostic markers are an increase in gene copy number or expression at chromosome 1q [28,29] and telomerase expression level [30,31]. Gene expression profiling also shows promise to identify new prognostic factors [32][33][34].…”
Section: Biological Prognostic Factorsmentioning
confidence: 99%
“…Approximately 15-20% of cases of Wilms tumour relapse, more frequently within the first 2-5 years following the primary diagnosis; in these cases, the risk of recurrence is mainly related to the morphological and molecular features of the previous tumour [12,8,18,7,14].…”
Section: Discussionmentioning
confidence: 99%
“…The association of chemotherapy and radiotherapy to radical nephrectomy has increased the overall survival rate up to 85-90% [3,6];however, in spite of these therapeutic improvements, tumour relapses in a subset of patients (15-20%) [12].Numerous studies have demonstrated that the risk of recurrence can be associated to different features such as histological tumour pattern and loss of heterozygosis (LOH) at 1p and/or 16q, as well as gain of chromosome 1 and other recently described alterations [8,18,7,14]. The recurrence risk is greater within the first 2 years after primary diagnosis (in these patients the percentage of survival approximaly ranges from 24% to 43%) but late relapses have occasionally been reported [1,10].…”
Section: Introductionmentioning
confidence: 99%